2015
DOI: 10.5993/ajhb.39.6.15
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Emotion Regulation Skills Facilitate Implementation of Health-related Intentions

Abstract: Findings are consistent with the hypotheses. Thus, skill-building trainings should support participants scoring low in ER skills in effectively coping with aversive affective states cued through skill-building exercises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…In the third session (realization), subjects learned how to overcome affective obstacles that created gaps between their intentions and behaviors ( Eckert et al, 2015 ). Eckert et al (2016) have shown that two emotion-regulation strategies are effective at reducing procrastination: tolerating aversive emotions and modifying them.…”
Section: Methodsmentioning
confidence: 99%
“…In the third session (realization), subjects learned how to overcome affective obstacles that created gaps between their intentions and behaviors ( Eckert et al, 2015 ). Eckert et al (2016) have shown that two emotion-regulation strategies are effective at reducing procrastination: tolerating aversive emotions and modifying them.…”
Section: Methodsmentioning
confidence: 99%
“…Difficulties in regulating emotions probably also play a critical role in procrastination. Indeed, the association between health-related intentions and actual health-related behaviors is moderated by emotion regulation skills, implying that managing emotions facilitates goal-directed behavior and task completion (Blunt & Pychyl, 1998; Eckert et al, 2015). Lastly, as our mediation SEM assessed relations among procrastination and multiple facets of mindfulness on a granular level, we decided to add trait mindfulness as a total score in our regression to assess the relative contribution of mindfulness as a singular construct in predicting procrastination.…”
Section: Secondary Aimmentioning
confidence: 99%
“…Aptaujas izveides laikā B daļai tika veikta izpētošā un apstiprinošā faktoru analīze (Berking & Znoj, 2008). Skalas uzrāda labu iekšējo saskaņotību (0.71 -0.83), atbilstošus retesta ticamības rādītājus (0.58 -0.76) (re-test reliability) (Berking & Znoj, 2008;Berking, Orth, Wuppermann, Meier, & Caspar, 2008a, Berking et al, 2008b, Berking, Meier, & Wupperman, 2010, Berking et al, 2011, Berking et al, 2012, Berking, Ebert, Cuijpers, & Hofmann, 2013, Berking, Wirtz, Svaldi, & Hofmann, 2014Eckert et al, 2015;Radkovsky et al, 2014;Wirtz et al, 2014;Fujisato et al, 2017;Grant et al, 2018, Vatan, & Oruçlular Kahya, 2018.…”
Section: Literatūras Apskatsunclassified